Perceptions, knowledge, attitude, practices and barriers towards research among Ayurveda interns: A cross - sectional pilot study - Arati Darvajkar; Urmila Shirke; Amruta Kakade; Asmita Wele; Jijaba Shirke (Journal of Ayurveda and Integrative Medicine, 2025)
Background: Research in Ayurveda takes the form of discovery of many scientific principles that guide innovations and evidence based clinical practice. It has been essential part of basic Ayurvedic education for over a decade, which provides ground for evaluation. Objective: This study aims to evaluate the perceptions, knowledge, attitude, practices and barriers towards research among Ayurveda interns, and to identify factors that may influence them. Methods: A cross sectional study was carried out between the period of September 30, 2023 and October 30, 2023 amongst Ayurveda interns from all over India. Data was collected using a validated questionnaire and disseminated via google forms. The questionnaire was based on Perception, Knowledge, Attitude, Practice and Barriers towards research domains. A total of 28 questions were included in the questionnaire. 21 questions were assessed using Likert scale, 3 questions with 1–10 Rating Scale and 4 questions were yes and no type. Results: A total of 199 participants from 31 different colleges and from 9 states responded to the survey. The mean age of study participants was 23.73 (SD = 1.854). Most of the students had a positive approach and willingness to participate in medical research, but the most challenging factor in maintaining their interest was mentoring and guidance. This survey highlights a few barriers like time constraints, insufficient motivation, mentorship gaps and limited awareness of sources of funding for research among Ayurveda graduates. Appropriate measures to overcome these barrier might be very useful in changing the perception, willingness and attitude of the students. Conclusion: Fresh graduates in Ayurveda are open to meaningful research if they can find competent mentors and guidance.